Community structure of parasitoids Hymenoptera associated with Brassicaceae and non-crop vegetation - YAHERWANDI YAHERWANDI (Smujo International, 2012)
Abstract. Yaherwandi. 2012. Community structure of parasitoids Hymenoptera associated with Brassicaceae and non-crop vegetation. Nusantara Bioscience 4: 22-26. Parasitoids Hymenoptera has an important role in agroecosystem because of their ability in suppressing pest population. Their presence in the field is seen as the key to agricultural ecosystem. Their presence can be influenced by the availability of non-crop vegetation. Some adult parasitoids Hymenoptera require food in the form of pollen and nectar of wildflowers to ensure effective reproduction and longevity. The objective of this research was to study communities of parasitoid Hymenoptera in Brassicaceae field and non-crop vegetation around Brassicaceae fields. Samplings were conducted at two different landscape structures, i.e. Kayu Tanduak and Padang Laweh representing complex landscapes, whereas Alahan Panjang and Sungai Nanam representing simple landscapes. Insects were sampled by three trapping techniques (farm crop, sweep net, and yellow pan traps) in one line of transect for each landscape. A total of 84 species from 17 families of parasitoids Hymenoptera were collected in Brassicaceae field and in non-crop vegetation. Landscape structure, flowering vegetation, and pesticide application affected the species richness, diversity and evenness of parasitoids Hymenoptera in Brassicaceae fields and non-crop vegetation.